A midcrustal ramp‐fault structure beneath the Taiwan tectonic wedge illuminated by the 2013 Nantou earthquake series. Issue 19 (7th October 2013) - Chuang, Ray Y.; Johnson, Kaj M.; Wu, Yih‐Min; Ching, Kuo‐En; Kuo, Long‐Chen
Abstract [1] Taiwan's active mountain belt is a spotlight for orogenic studies and was first used to test the critical‐taper wedge mechanics. The concept of an orogenic wedge above a shallow detachment surface has been highly influential on current understanding of orogenic processes in Taiwan. However, the recent ML 6.2 and ML 6.5 2013 Nantou reverse‐faulting earthquakes in central Taiwan have nucleated below the proposed detachment, indicating that active mountain building is occurring below the orogenic wedge. We estimate the coseismic slip distributions and fault geometry using the uniform stress drop slip inversions. The earthquakes occur on essentially the same 30° dipping fault plane ramping up from 20 km depth near a cluster of 1999 Chi‐Chi earthquake aftershocks to the shallow detachment and the Chi‐Chi fault plane. The fault could be a deep extension of a mature shallow fault or a newly developed deep ramp fault that is not reflected in the surface geology.